ABHD11 maintains 2-oxoglutarate metabolism by preserving functional lipoylation of the 2-oxoglutarate dehydrogenase complex - Peter S. J. Bailey (Nature Portfolio, 2020)
2-oxoglutarate links mitochondrial metabolism to oxygen sensing, gene transcription and epigenetic modifications. Here, the authors describe a mutagenesis screen to find genes that control 2-oxoglutarate levels, and identify ABHD11 as a mitochondrial regulator of 2-oxoglutarate abundance.